Microscopy of oxidation proceedings of the first international conference held at the University of Cambridge, 26-28 March 1990 - Bennett, M. J. 1933-; Lorimer, G. W. (Institute of Metals, 1991)
Covers the reaction processes from oxide failure nucleation, through scale growth, as well as the possibilities of alloy design for improved oxidation resistance using a wide range of microscopical techniques.
"Sponsored and organised by the Materials Science Division of the Institute of Metals with the co-sponsorship of the Institute of Physics and the Royal Microscopical Society."
"The First International Conference on the Microscopy of Oxidation was held at Selwyn College, Cambridge"--Preface.
Keywords: Corrosion and anti-corrosives -- Congresses.; Oxidation -- Congresses.; elektronické knihy; electronic books